Improving Frontline Responses to Domestic Violence in Europe (University of Maribor Press, 2021)
The monograph on improving the response of first responders to domestic violence in Europe aims to identify gaps in the cooperation of first-line responders and deliver recommendations, toolkits and collaborative training for European police organizations and medical and social work professionals. The goal is to improve integrate institutional response to domestic violence. Shared training and adequate risk assessment tools will create a positive feedback loop, increasing reporting rates of domestic violence to police, the medical profession, and community and social work practitioners. IMPRODOVA | Improving Frontline Responses to High Impact Domestic Violence This project has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No 787054.